2002
DOI: 10.4269/ajtmh.2002.66.52
|View full text |Cite
|
Sign up to set email alerts
|

Identification of virulence-associated antigens and plasmids in Rhodococcus equi from patients with acquired immune deficiency syndrome and prevalence of virulent R. equi in soil collected from domestic animal farms in Chiang Mai, Thailand.

Abstract: Abstract. The prevalence of virulent Rhodococcus equi in soil collected from 17 domestic animal farms (from 12 cattle, 1 pig, and 4 horse farms) and in 6 clinical specimens from patients with acquired immune deficiency syndrome (AIDS) in Chiang Mai, Thailand, was investigated. The isolates were tested for the presence of 15-17-kDa antigens (VapA) and a 20-kDa antigen (VapB) by immunoblotting and for the presence of virulence plasmid DNA. Rhodococcus equi was isolated from most soil samples (68 of 80) obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…It has been demonstrated that R. equi strains from pigs may express VapA or VapB, which are characteristic for strains from AIDS patients (Takai et al, 1996;Makrai et al, 2002;Takai et al, 2002). This raised questions about the zoonotic potential of R. equi and increased interest in further research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that R. equi strains from pigs may express VapA or VapB, which are characteristic for strains from AIDS patients (Takai et al, 1996;Makrai et al, 2002;Takai et al, 2002). This raised questions about the zoonotic potential of R. equi and increased interest in further research.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the protein profiles, plasmid characteristics, and virulence levels of these strains have been described previously [5, 7, 10, 11]. …”
Section: Methodsmentioning
confidence: 99%
“…In Thailand, infection by R. equi has been reported in patients with and without HIV infection in Chiang Mai, and 52 isolates from 69 sporadic cases collected between 1993 and 2001 were VapB-positive R. equi [10, 11]. Isolates of VapB-positive R. equi collected from healthy pigs at an abattoir and from immunodeficient patients in Chiang Mai contained the same plasmid types [11], so the pig was thought to be a source of VapB-positive R. equi infections in immunocompromised patients [5, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. equi has been isolated from feces and soil at various isolation rates (4,(14)(15)(16). R. equi culture positivity rates were reported as 68%-86% (16), 86% (17), and 95% (15) from soil samples. On the other hand, Takai et al reported 72%-92% culture positivity for R. equi in equine feces (9).…”
Section: Discussionmentioning
confidence: 99%